Difficult tolerance: : A Ricoeurian account and some practical theological reflections - Dreyer, Jaco (Stellenbosch Theological Journal, 2018)
The aim of this article is to present Ricoeur's view on tolerance, and to reflect on some implications of his view for practical theology in South Africa. I start with a very brief introduction of tolerance as a key principle of liberal democracy and refer to the political use of tolerance in the transition to a democratic South Africa. After clarifying the aims and location of this article, I present Ricoeur's view on tolerance as an ongoing and challenging task for a capable subject. The last section is a brief reflection on some implications of Ricoeur's view of difficult tolerance for practical theology as an academic discipline in (South) Africa. :Tolerance is a tricky subject: too easy or too difficult" (Ricoeur 1996b:1)